Pengaruh Jumlah Foto dan Shutter Speed terhadap Penyimpangan Dimensi Hasil Pemindaian Objek pada Proses Reverse Engineering dengan Teknik Fotogrametri - Khoirul Anwar Rifa’i; Wirawan Wirawan (International Forum of Researchers and Lecturers, 2025)
Photogrammetry is a widely used technique in reverse engineering that utilizes photographs taken from multiple angles to capture the geometric structure and surface textures of physical objects. This method has gained popularity due to its cost-effectiveness and time efficiency compared to more expensive alternatives such as laser scanning. However, one of the primary limitations of photogrammetry is its susceptibility to dimensional deviations that can affect the accuracy of the resulting 3D model. Among the influential parameters, the number of photos taken and the camera’s shutter speed play a crucial role in determining the level of geometric precision. This study aims to analyze the effect of the number of photos and shutter speed on dimensional deviation in 3D reconstruction results. It also seeks to determine the optimal combination of these parameters to enhance model accuracy in reverse engineering applications. The research method used is an experimental approach, in which variations of photo quantity and shutter speed are applied during image capture. The resulting photographs are processed into a 3D model using Computer-Aided Design (CAD) software and compared with the actual dimensions of the object under study. The findings reveal that both the number of photos and shutter speed significantly influence dimensional accuracy, both individually and interactively. The best results were obtained using a combination of 48 photos with a shutter speed of 0.020 seconds, yielding the smallest deviation of 7.6 mm. In contrast, a combination of 36 photos with the same shutter speed produced the highest deviation at 10.6 mm. ANOVA analysis yielded a p-value < 0.05 and an R² value of 94.21%, confirming the importance of selecting appropriate imaging parameters for accurate photogrammetry outcomes.